Analisis Praktik Jual Beli Beras Di Madura Dalam Perspektif Bisnis Islam - Masduki; Fadoilatul Akmal (Program Studi Perbankan Syariah Institut Al-Fithrah (IAF) Surabaya, 2024)
Buying and selling is a social activity, and goods are traded have sizes and measurements. To count the number of objects in muamalah activities require a tool to measure it so that the number of the object is known clearly and with certainty. This type of research uses a qualitative descriptive method. The results of the data obtained by the author are observed and combined with existing theories. The method used is interviews, documentation, and this research also uses observational research related to data collection methods where the research records information as the author witnessed during the study. The analysis in this discussion is descriptive-qualitative analysis. This research is expected for rice traders to know more about the implementation of buying and selling in accordance with Islamic economics, because Islamic economics is an economy that in carrying out activities based on and guided by the Qur'an and As-Sunnah, so as to create healthy trade, and It is hoped that traders must always remember that the consequences of dishonesty will be rewarded by Allah swt. in the hereafter. The results of this study indicate that the mechanism of buying and selling rice in the Arosbaya market has not been carried out correctly according to Islam. Because there are some rice sellers who sell rice dishonestly, and there are still traders who still reduce the rice scales, in order to get a bigger profit. The sale and purchase of rice carried out at the Arosbaya market is still not in accordance with Islamic business ethics. Because there are still principles of Islamic business ethics that are violated, namely the principles of monotheism, responsibility, justice, truth or honesty, freedom and sincerity.